Serological Diagnosis of Subclinical Gluten Enteropathy: A Case Presented As Treatment Resistant Osteomalacia - Aynur Başaran,; Kıymet İkbal Karadavut,; Ece Aydoğ,; Aytül Çakcı, (Archives of Rheumatology, 2006)
Gluten enteropathy is frequently presented with minimal symptoms and signs. Atypical clinical presentation and treatment resistant osteomalacia should be screened for gluten enteropathy. Current serologic diagnostic methods have a high sensitivity and specificity. Serologic screening is recommended even in the absence of clinical symptoms and presence of minor histopathologic findings. In this case we report a patient with treatment resistant osteomalacia due to subclinical gluten enteropathy that responded to gluten free diet. (Rheumatism 2006; 21: 118-20)